Readiness of the Philippine Agriculture and Fisheries Sectors for the 2015 ASEAN Economic Community: A rapid appraisal - Ramon L. Clarete; Isabela Rosario G. Villamil (Philippine Institute for Development Studies (PIDS), 2015)
The ASEAN Economic Community (AEC) transforms the ASEAN region into a single market and production base by 2015. This promotes greater competition for the Philippine agriculture and fisheries (A and F) sectors. With the country's A and F sector lagging behind its neighboring ASEAN countries, there are fears that local industries will be displaced. The Global Trade Analysis model suggests an increase in both imports and exports as an impact of tariff reforms. The sectors ready for integration include mangoes, bananas, and pineapples. For the coconut sector, intensification of planting, replanting, and product diversification are needed to enhance and maintain supply. Production increase for perishable commodities, such as onions and meats, entails the need for lower power costs. With corn as a potential export commodity, cultivation areas are being expanded and agricultural policies are being aligned with the policies of the ASEAN Free Trade Agreement. To reap the benefits from the AEC, several measures must be performed, i.e., diversification and product quality upgrading. Public support must focus on providing adequate infrastructure, general services, research and development, and extension programs. Particularly, this paper recommends modernizing the country's value chains in the A and F sector to effectively mobilize A and F exports into the ASEAN market. This is done by creating industry road maps to equip major stakeholders knowledge on market opportunities; organizing the value chains and effectively assisting their various participants to comply with international trade product standards, processes, and regulations; building capability for effectively managing the risk of disputes among value chain participants; and promoting the cooperation among farmers, small and medium enterprises, and large enterprises within these agro-based value chains.
Keywords: 330; Asean Economic Community; value chain; agriculture and fisheries; tariff reforms